Coinfection of SARS-CoV-2 and influenza A (H3N2) detected in bronchoalveolar lavage fluid of a patient with long COVID using metagenomic next−generation sequencing: a case report - Liang, Xuefei; Wang, Qiushi; Liu, Jia; Ma, Jing; Zhang, Yajuan; Wang, Meng; Yu, Yang; Wang, Linlin (Frontiers in Cellular and Infection Microbiology, 2023)
The growing number of long COVID cases has drawn clinical attention to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which has been spreading worldwide since winter 2019. Its symptoms are not limited to fatigue and shortness of breath but also affect daily life. We report the use of metagenomic next-generation sequencing (mNGS) to detect coinfection with SARS-CoV-2 and influenza A virus in a patient with long COVID. The patient was admitted with fever, expectoration, fatigue, and shortness of breath. The PCR test was negative due to possible clearance of SARS-Cov-2 in the upper respiratory tract of patients with long COVID. Other routine microbiological tests were also negative, making the clinical diagnosis difficult. Bronchoalveolar lavage fluid (BALF) samples were tested using mNGS. The patient was diagnosed and treated promptly, recovered quickly, and continued taking azvudine after discharge; his condition was stable. This study illustrates that mNGS may be valuable for the timely diagnosis of patients with long COVID and their mixed infections.